Primary multivessel occlusions treated with mechanical thrombectomy - Kaesmacher, Johannes; Meyer, Lukas; Styczen, Hanna; Lobsien, Donald; Seker, Fatih; Piechowiak, Eike; Tan, Benjamin Y.Q.; Fischer, Sebastian; Clajus, Christin; Yeo, Leonard; Papanagiotou, Panagiotis; Kastrup, Andreas; et al. (Stroke, 2020)
Background and Purpose: Acute ischemic stroke caused by primary multivessel occlusions (pMVO) is a rare but devastating disease. Whether multi-target mechanical thrombectomy for pMVO is beneficial remains unknown. Methods: Multicenter retrospective review of patients treated with multi-target mechanical thrombectomy. The following pMVO sites were included: basilar artery, internal carotid artery, and middle cerebral artery (M1 and M2). Baseline characteristics were reported together with interventional technique, technical efficacy, and safety parameters. Clinical outcomes were evaluated applying the National Institutes of Health Stroke Scale and modified Rankin Scale. A systematic literature review was performed to summarize previous reports on pMVO mechanical thrombectomy. Results: Of 6081 patients screened, 21 patients met the inclusion criteria (0.35% [95% CI, 0.23%-0.53%]). In 70% (14/20) a cardioembolic cause was reported. A successful reperfusion of Thrombolysis in Cerebral Infarction scale score ≥2b was achieved in 95.2% (20/21) for the first and 76.1% (16/21) for the second target vessel. In those who survived the acute hospital stay (n=10/21), median admission National Institutes of Health Stroke Scale improved from 21 (interquartile range, 13-27) to 8 (interquartile range, 2-20) at discharge (P=0.006). Mortality was 60% (12/20) at 90 days and only 20% (4/20) of patients reached modified Rankin Scale score ≤2. Acceptable outcomes were almost exclusively observed in pMVO patients presenting with at least one M2 occlusion.Conclusions: Multi-target mechanical thrombectomy for pMVOs is rarely performed; however, the procedure appears to be feasible and safe with high reperfusion rates for both occlusion sites. More than half of all treated patients deceased early and favorable outcomes may only be expected for pMVO patients including at least one M2 occlusion.
Gesehen am 29.10.2020